Maximum Information Securing Techniques With Vigenere Custom-Based Encryption - Sugiono; Ahmad Fauzi; Dini Nurlaela; Lestari Yusuf (Jurnal Mantik, 2022)
The Vigenere algorithm is one of the classic encryption algorithms that is easy to understand and apply in the process of securing information. By using the vigenere table we can easily read messages that have been encrypted. However, the vigenere algorithm is also an algorithm that is difficult to solve, this is because to be able to solve a cipher text, a key is needed. With a character transition technique based on the sequence of characters in a certain key so that the transition form of the character becomes unstable and difficult to guess. The vigenere method in general is still not optimal because it only relies on keys to secure information, while the vigenere table used is still a standard alphabet that has been applied by vigenere and is still incase sensitive or case sensitive. In this study we will maximize the use of the vigenere algorithm by randomizing the predetermined vigenere alphabet table so that a key and table form are needed to be able to solve a ciphertext